Heterogeneous expectations and housing market - Huang, Zichun (2017)
This thesis studies the boom-bust housing price dynamics under heterogeneous expectations. I mainly focus on three key questions: (1) Why some housing prices form an exponential pattern and others follow a linear trend? (2) How to provide an explanation not only for the formation but also for the subsequent collapse of an exponential bubble and a linear trend jointly within the same framework? (3) How do different market conditions affect the trading behavior of market participants in the US housing market?